ANTI-BIOTIC RESISTANCE PROFILE OF STRAINS OF PSEUDOMONAS AERUGINOSA EXTRACTED FROM HOSPITAL SPECIMENS IN A TERTIARY CARE FACILITY - Balani , Jayant (Journal of Biomedical and Pharmaceutical Research, 2018)
Background: Pseudomonas aeruginosa, often known as Ps. aeruginosa, is a significant bacterial pathogen that has been identified from a variety of specimens. The emergence of a wide range of anti-microbial drugs with anti-pseudomonal activity and advancements in medical and surgical management have not stopped the life-threatening illness caused by Pseudomonas aeruginosa from causing difficulties in hospital acquired contaminations. Anti-biotic resistance in hospital isolates is rising, according to a number of epidemiological studies. Material and Technique: One year was dedicated to the conduct of this investigation. A total of 1840 specimens were analyzed during this time, and 1162 of those specimens revealed bacterial growth. 200 hospital isolates of Pseudomonas aeruginosa were obtained from 1162 specimens. The specimens were chosen based on how well they grew on standard Mac Conkey medium, where lactose non-fermenting pale colonies with positive oxidase tests were seen, and on Nutrient Agar, where lactose non-fermenting pigmented and non-pigmented colonies also showed positive oxidase tests. The Modified Kirby Baur disc diffusion technique (disc-diffusion) was used to determine the anti-microbial vulnerability of each isolate in accordance with CLSI standards. Result: The majority of Ps. aeruginosa isolates found in the current investigation are extremely resistant to cefepime (86%) piperacillin (80%), and ceftriaxone (66%). Comparing piperacillin alone to piperacillin-tazobactam combination, low level resistance (50%) was observed. Conclusion: Strict anti-biotic policies are essential to stop the spread of resistance bacteria, and contamination control measures and multidrug resistant organism surveillance programs must be put in place. Keywords: Anti-biotic Resistance, Cefepime, Pseudomonas aeruginosa